2020
DOI: 10.1016/j.isci.2020.101523
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Huwe1 Is Essential for Oocyte Maturation and Preimplantation Embryo Development

Abstract: Summary HUWE1 is a HECT-domain ubiquitin E3 ligase expressed in various tissues. Although HUWE1 is known to promote degradation of the tumor suppressor p53, given a growing list of its substrates, in vivo functions of HUWE1 remain elusive. Here, we investigated the role of HUWE1 in the female reproductive system. Homozygous deletion of Huwe1 in mouse oocytes of primary follicles caused oocyte death and female infertility, whereas acute depletion of HUWE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Live-cell protein masking by antibodies was introduced in the 1980s to show the effects of disrupting the cytokeratin filament network in mouse embryos 42 , while the antibody-based proteasomal degradation of proteins is more recent. Known as ‘ Trim-away’ , it was introduced in 2017 and it has been applied by several laboratories 14,43-47 including our own 15,16 to tackle various proteins of the mammalian oocyte or embryo. In many of those cases the degradation of target protein was partial 43,44,48,49 , yet a knockdown was sufficient to produce a bold effect, as seen here also with ZP3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live-cell protein masking by antibodies was introduced in the 1980s to show the effects of disrupting the cytokeratin filament network in mouse embryos 42 , while the antibody-based proteasomal degradation of proteins is more recent. Known as ‘ Trim-away’ , it was introduced in 2017 and it has been applied by several laboratories 14,43-47 including our own 15,16 to tackle various proteins of the mammalian oocyte or embryo. In many of those cases the degradation of target protein was partial 43,44,48,49 , yet a knockdown was sufficient to produce a bold effect, as seen here also with ZP3.…”
Section: Discussionmentioning
confidence: 99%
“…Known as ‘ Trim-away’ , it was introduced in 2017 and it has been applied by several laboratories 14,43-47 including our own 15,16 to tackle various proteins of the mammalian oocyte or embryo. In many of those cases the degradation of target protein was partial 43,44,48,49 , yet a knockdown was sufficient to produce a bold effect, as seen here also with ZP3. In fact, the phenotype of the ZP3 knockdown - pronuclear arrest - was even more severe than that incurred after epitope masking of ZP3: the zygotes not only arrested but also died.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these two answers predict that a complete depletion by TRIM21-mediated proteasomal degradation may not work, and may not be required to work (depending on one's aim), for every protein. Indeed, it may be noted that out of thirteen studies which applied the TRIM21-mediated proteasomal degradation on oocytic or embryonic proteins in mammals 21,22,27,[65][66][67][68][69][70][71][72][73][74] , four studies reported complete depletion (ITPR1 67 ; SNAP23 27 ; G6PD, PKM, GFPT1 65 ; EG5 also known as KIF11 21 ), four studies reported almost complete depletion (BTG4 68 ; TACC3 69 ; RACGAP1 also known as CYK4 and PLK1 70 ; SMC3 72 ) and five studies reported incomplete depletion (RCC1 66 ; CENPF 71 ; TEAD4 22 ; aPKC also known as PRKC 73 ; HUWE1 74 ). Thus, complete removal of the protein of interest seems to be more the exception than the rule (with current technology).…”
Section: Discussionmentioning
confidence: 99%
“…These studies collectively revealed that HUWE1 plays important roles in spermatogonial differentiation by orchestrating DNA damage responses. During oocyte maturation and preimplantation embryo development, oocyte-specific HUWE1 deletion was found to cause oocyte death and female infertility in mice, which were not rescued by p53 deletion, suggesting that another HUWE1 substrate might contribute to this pathway (Eisa et al, 2020).…”
Section: Huwe1 Promotes Protein Degradation During Spermatogenesis An...mentioning
confidence: 99%